Being True, Sounding False - John T. Lysaker (European Journal of American Studies)
The essay explores multiple senses of “true,” arguing that truth not only has a performative sense, but that certain performances can themselves be true as when a friend is a true friend. Taking that thought in a metaphilosophical direction, the essay also argues that writing can be true to philosophy or sound false on those terms.